The theory of exchange - Newman, Peter (Englewood Cliffs, N.J. : Prentice-Hall, 1965)
This book presents a comprehensive account of the elementary theory of the exchange of commodities, and has been written out of the author's conviction that existing discussions of this important topic in economic treatises reflect neither the richness nor the rigor of which modern economic theory is capable. As a text, the book could serve as a supplement for the upper division or graduate price theory course, and as introductory to courses on mathematical economics and on international trade theory.
Includes bibliographical references and index.
rpm 29/09/2017
Loans
Keywords: Exchange